Epistemological foundations of Murray Bowen's Theory - Nascimento Otto, Ana Flavia (2022)
The article aims to present the epistemological foundations of Murray Bowen's Theory, addressing the historical-scientific context of its emergence and its epistemological bases. In addition, its current status in the field of Family Therapy is discussed, listing several studies that prove hypotheses raised by this scientist in the 70s. In conclusion, the importance of Bowen's contributions to the understanding of human development in various fields of application of his theory, especially in the field of family therapy.